STRATEGI INVESTASI XIAOMI INC DALAM PERSAINGAN PASAR SMARTPHONE DI INDONESIA TAHUN 2014-2018 - Bayu Anggara; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research is about international political economy or international trade centered on companies from a country in establishing a cooperation. In this study, the authors took a discussion of the strategy carried out by a Chinese company, namely Xiaomi.This research focuses on finding out how the strategies are carried out by Xiaomi in smartphone competition in Indonesia. This is interesting because the results in front of xiaomi are able to compete very well and can continue to this day.The source taken in this study are directly from the official website itself and also from various other sources such as books and online websites. Xiaomi is able to survive in the smartphone competition in Indonesia and can launch various strategies to gain consumer interest with its products.Many other smartphone venders are also afraid of the strategies being carried out by xiaomi because xiaomi is able to make many people choose their products Keyword : strategy, smartphone, xiaomi, competition